Mammals of the Natural National Park Selva de Florencia, Caldas, Colombia - Ramírez-Chaves, Héctor E.; Velásquez-Guarín, Daniela; Ocampo-Velásquez, Juan D.; Mejía-Fontecha, Ingrith Yuliany; Acosta, Amilvia; Colmenares-Pinzón, Javier E.; Castaño, John Harold; Roncancio Duque, Néstor (THERYA, 2021)
The Department of Caldas, Central Andes of Colombia, has two National Natural Parks protecting strategic Andean ecosystems. However, the available information on mammals in these protected areas has not been compiled or updated recently. Here, we present an updated inventory of the mammals present in the Selva de Florencia National Natural Park. To construct the inventory, we used historical (museum vouchers) and recent records obtained during field activities over the last 20 years. We used several trapping methods including Sherman and Tomahawk traps, mist nets, and camera traps. We documented 81 mammal species belonging to nine orders, 25 families and 59 genera. Bats (Chiroptera: 30 spp.), rodents (Rodentia: 17 spp.), and carnivores (Carnivora: 13 spp.) were the most diverse groups, representing 73.2 % of recorded species. We also recorded orders such as Didelphimorphia (8 species), Primates (5), Pilosa (3), Artiodactyla (2), Cingulata (2), and Eulipotyphla (1). Also, we recorded two endemic species (Marmosops chucha and Cryptotis colombianus) and two new species for the Department of Caldas (Bassaricyon neblina and Heteromys aff. anomalus). These species constitute elements of the Andean region and the Nor-Andean and Chocó-Magdalena biogeographic provinces. We highlight the presence of four endangered primates (Aotus lemurinus, Ateles hybridus, Cebus versicolor, and Saguinus leucopus), two of which are endemic to Colombia: S. leucopus and C. versicolor. This work is the baseline to update the management plan of the protected area, from the review of its conservation targets, the definition of the specific management goals, to its effective monitoring.